Revalorisation of brewer’s spent grain for biotechnological production of hydrogen with Escherichia coli - Cabrera, Gema; Jáimez, José Manuel; Sánchez-Oneto, Jezabel; Bolivar, Jorge; Valle, Antonio (Frontiers in Bioengineering and Biotechnology, 2024)
Agro-industrial wastes are generated in huge amounts triggering damages to the environment and human health, therefore, there is a necessity for its revalorisation into high-value compounds including biofuels. One of these food wastes is the brewer´s spent grain (BSG) obtained from the beer industry, which is produced in vast quantities worldwide. The rich-fibre and protein content of BSG is a waste of this valuable resource and the main challenge of this approach is to make the carbohydrates and proteins contained available for bacteria metabolization into high-value products.This work aims to optimise a thermal-hydrolysation process to revalorise BSG for the biotechnological conversion into hydrogen (H2), as a clean energy that can replace fossil fuels.Firstly, it was used a 2k full factorial design method for hydrolysation of BSG and showed that temperature and acid concentration are significant factors that affect the extraction of reducing sugars (RS) and proteins. After steepest ascent, and central composite design (CCD) statistical methods, it was determined that the optimised condition is 0.047 M H2SO4, 150 ºC, 30 min and 15% BSG leading to the theoretic concentration of 54.8 g RS/L and 20 g/L proteins. However, HMF was generated in thermal-hydrolysis conditions at higher temperatures than 132ºC. Therefore, a screening of HBSGs fermentation using Escherichia coli was performed in order to analyse the most suitable conditions to produce more H2, volatile fatty acids (succinate and acetate) and ethanol. The fermentation of HBSG A17 condition (117ºC, 20 min, and 0.1 M H2SO4) produced the highest H2 production (48 mmol/L) in this work. This study is very helpful to further select the most feasible BSG pre-treatment depending on the biotechnological application.